2012
DOI: 10.3109/01480545.2012.720989
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lipid damage related to pathological and physiological conditions

Abstract: Several diseases and xenobiotics are known to generate reactive species that may trigger oxidative stress when not properly scavenged by the antioxidant defenses and result in tissue damage. We investigated lipid peroxidation (LPO) as a possible mechanism for tissue damage in some pathologies, in the normal aging process, and in subjects exposed to organic solvents. Plasmatic malondialdehyde (MDA) was quantified by high-performance liquid chromatography with visible wavelength detection in 239 subjects and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…NO reacts with superoxide to produce peroxynitrite. The free radical, superoxide, which is highly increased during reperfusion, contributes to cardiac damage in two ways: First, it decreases the amounts of the cardioprotective NO, and second, it produces the powerful oxidant agent, peroxynitrite, with damaging effects on the heart (Yasmin et al, ; Garcia et al, ). Antioxidants, in general, remove superoxide ions, and therefore increase the availability of NO (Mackness et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…NO reacts with superoxide to produce peroxynitrite. The free radical, superoxide, which is highly increased during reperfusion, contributes to cardiac damage in two ways: First, it decreases the amounts of the cardioprotective NO, and second, it produces the powerful oxidant agent, peroxynitrite, with damaging effects on the heart (Yasmin et al, ; Garcia et al, ). Antioxidants, in general, remove superoxide ions, and therefore increase the availability of NO (Mackness et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…MDA is generally believed to originate under stress conditions, and now it has been found to have high capability of reaction with multiple biomolecules such as proteins or DNA that leads to the formation of adducts [27]. It is further reported that excessive MDA production have also been found to be associated with different pathological states [28][29][30][31]. Hence, higher anti-inflammatory activity in SGE of H. dromedarii ticks might have helped the ticks to feed better by controlling inflammatory response mediated vasoconstriction during tick bite which is also in accordance with increased free radical scavenging activity and overall antioxidant status in these ticks.…”
Section: Discussionmentioning
confidence: 99%
“…Both Sp1 and Sp3 can interact with and recruit a large number of proteins including the transcription initiation complex, histone modifying enzymes, and chromatin remodeling complexes, which strongly suggest that Sp1 and Sp3 are important transcription factors in the remodeling chromatin and the regulation of gene expression [75]. On the other hand, MDA production by nonenzymatic processes remains poorly understood despite their potential therapeutic value, because this MDA is believed to originate under stress conditions and has high capability of reaction with multiple biomolecules such as proteins or DNA that leads to the formation of adducts [76–78], and excessive MDA production have been associated with different pathological states [79–85] (see Table 1). Identifying in vivo MDA production and its role in biology is important as indicated by the extensive literature on the compound (over 15 800 articles in the PubMed database using the keyword “malondialdehyde lipid peroxidation” in December 2013).…”
Section: Lipids Damage By Reactive Oxygen Speciesmentioning
confidence: 99%